Low density parity check (LDPC) for space time frequency coding in MIMO-OFDM - Abdullah, Ezmin (2013)
MIMO-OFDM offers significant high data rates transfer without increasing the bandwidth or transmit power. By adopting diversity coding such as Space Time coding (STC), Space Frequency Coding (SFC), Space Time Frequency Coding (STFC), the major challenge of transmitting information over a long distances can be improved in terms of reliability and security of the data due to ISI and ICI. Low Density Parity Check which is introduced by Gallager in 1962 has attracted much attention to the needs of efficient and reliable coding theory in digital data communication system. In this paper together with STFC, the simulation of LDPC under 8, 16 and 64 QAM is conducted in 4x4 MIMO-OFDM over Additive White Gaussian Noise (AWGN) and Raleigh fading channel. The propose system is analyzed based on BER with signal to noise ratio (SNR). The simulation using Matlab, shows the BER comparison between AWGN and Rayleigh fading channel which LDPC works better in Rayleigh fading channel while in digital modulations the system outperforms with 8-QAM . The performance of LDPC between MIMO-OFDM and MISO OFDM is also being compared and it is further prove that MIMO performs better than MISO [1].